Morphological remodeling during recovery of the neuromuscular junction from terminal Schwann cell ablation in adult mice - Hastings, Robert Louis (Sci Rep, 2020)
Schwann cells (SCs) are integral to the formation and function of the peripheral nervous system (PNS). Exemplifying their importance, the loss or dysfunction of SCs is a feature of a myriad of diseases and conditions that compromise the PNS. Thus, it remains essential to understand the rules that govern the proliferation, differentiation and reconnection of Schwann cells with peripheral axons. Here, we examined the consequences of locally and acutely ablating terminal Schwann cells (tSCs) at the adult mouse neuromuscular junction (NMJ) by using mice expressing diphtheria toxin receptor (DTR) preferentially in tSCs compared to myelinating SCs followed by local application of diphtheria toxin (DTX). After DTX application, tSCs died but, importantly and contrary to expectations, their associated motor axons did not fully degenerate. Within 3 weeks, tSCs returned and reestablished coverage of the synapse with increased numbers. Furthermore, the post-synaptic muscle fibers displayed increased distinct clusters of acetylcholine receptors and axon terminals exhibited numerous terminal varicosities. The lack of degeneration of bare motor axon terminals and the morphological remodeling that occurs upon the return of tSCs to the NMJ may have wider implications for the mechanisms governing tSC occupancy of the adult NMJ and for conditions that adversely affect tSCs.